Controlling the burst release of doxorubicin from polymeric depots via adjusting hydrophobic/hydrophilic properties - Chitinart Thedrattanawong (2019)
© 2018 Elsevier B.V. The control of initial burst release of drugs from polymeric depots is a promising approach to achieve the dose level of therapeutic agents after administration. This study describes the method to control initial burst release of doxorubicin (Dox) from injectable polymeric depots made from PLGA 70:30, by modifying the weight ratio between protonated and deprotonated Dox that were incorporated into the depots. High initial burst release within 24 h was found at 86.6 ± 5.3% in depots incorporating with 100% protonated Dox. Burst release values were dramatically reduced to 48.5 ± 2.5, 41.8 ± 1.5, 35.1 ± 2.4, 27.3 ± 2.9, and 22.0 ± 2.1% when protonated Dox ratio was reduced to 98.75, 97.5, 95, 90, and 85%, respectively. To investigate the released Dox activity, cell viability of human hepatocellular carcinoma cells (HepG2) treated with extracted medium from 100 to 85% protonated Dox-loaded depots were 5.81 ± 1.11% and 7.44 ± 0.72%. Results show that the high burst release was reduced when deprotonated Dox was used. SEM confirmed the mechanism of Dox release from PLGA depots. The incorporation of deprotonated Dox could be a promising method in controlling drug release from polymeric depots for cancer treatment in the future.